1999
DOI: 10.1152/ajpheart.1999.277.1.h268
|View full text |Cite
|
Sign up to set email alerts
|

Reduced coronary NO production in conscious dogs after the development of alloxan-induced diabetes

Abstract: The role of nitric oxide (NO) in the control of coronary blood flow (CBF) during the development of diabetes is unknown. To study this, mongrel dogs were chronically instrumented using sterile techniques for measurements of systemic hemodynamics and CBF. With heart rate controlled (150 beats/min), veratrine (1–10 μg/kg) caused dose-dependent increases in CBF; e.g., 5 μg/kg of veratrine increased CBF by 57 ± 7% from 41 ± 1.3 ml/min ( P < 0.05). The dogs developed diabetes 4–5 wk after injection of alloxan (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
45
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 34 publications
4
45
0
Order By: Relevance
“…Endothelial dysfunction is believed to play a key role in the early development of atherosclerosis and precedes plaque development [2]. Experiments carried out in animal models of diabetes have shown impaired endothelium-dependent vasomotion [3]. Blood flow responses to endothelial NO-dependent vasodilators, for example acetylcholine, are characteristically impaired in patients with diabetes [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial dysfunction is believed to play a key role in the early development of atherosclerosis and precedes plaque development [2]. Experiments carried out in animal models of diabetes have shown impaired endothelium-dependent vasomotion [3]. Blood flow responses to endothelial NO-dependent vasodilators, for example acetylcholine, are characteristically impaired in patients with diabetes [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is well established that oxygen-derived free radical production, which is increased in diabetes (8,9), could impair endothelium-dependent vasodilation since it has been proved that superoxide anions could inactivate nitric oxide (10). Lastly, several studies have shown that nitric oxide production was reduced in diabetes in both peripheral and coronary vascular beds (11,12).We had previously demonstrated that a low dose of deferoxamine (DFX), an iron chelator that prevents ironcatalyzed generation of hydroxyl radicals, restored normal dilation of epicardial coronary arteries in diabetic patients, suggesting that inactivation of nitric oxide by oxygen species may play a role in impairment of coronary vasomotion (13). Similar results have been obtained in peripheral circulation by antioxidant therapy (14 -17).…”
mentioning
confidence: 99%
“…On the other hand, it is well established that oxygen-derived free radical production, which is increased in diabetes (8,9), could impair endothelium-dependent vasodilation since it has been proved that superoxide anions could inactivate nitric oxide (10). Lastly, several studies have shown that nitric oxide production was reduced in diabetes in both peripheral and coronary vascular beds (11,12).…”
mentioning
confidence: 99%
“…(7,8), in chronically instrument-implanted dogs before and after induction of diabetes with alloxan monohydrate (40 -60 mg/kg i.v.) (21).…”
mentioning
confidence: 99%
“…After nondiabetic control experiments were conducted, alloxan monohydrate (40 -60 mg/kg) was administered intravenously over 1 min to induce diabetes (21). Alloxan was prepared as a 5% solution in citrate buffer (pH 4.0 -4.5).…”
mentioning
confidence: 99%